Educación para la crianza en un programa de atención a la niñez: lecciones para la salud pública. - Peñaranda C., Fernando; Bastidas A., Miriam; Torres E., Nicolás; Trujillo D., Johanna; Otálvaro-Orrego, Jaider Camilo (Revista Facultad Nacional de Salud Pública)
This is a study of the educational process of Colombian Family Welfare Institute (in Spanish, Instituto Colombiano de Bienestar Familiar-ICBF) program named family woman and infancy (in Spanish, Familia, Mujer e Infancia-FAMI). Furthermore, it is a valuable experience for the healthcare sector from which it must learn parenting teaching. ICBF's first infancy educational pedagogical community project systematization was conducted including FAMI mother's pedagogical practices. Information was collected and analyzed at meetings and workshops, and it was complemented interviewing FAMI mother's and ICBF personnel individually and in groups. This study presents findings regarding the importance of education in the FAMI program, the pedagogical proposal, its implementation, parenting teaching, and the way FAMI mothers' actions are perceived. This study also conducts a pedagogical analysis of the educational model. Furthermore, the study presents the different types of learning that could be implemented in Healthcare programs which have parenting teaching.